Perencanaan Tebal Overlay dengan Alat Benkelman Beam dan Falling Weight Deflectometer - Mukhlis, Amir; Agustiar, Agustiar (Tameh, 2021)
In a certain period, the road pavement will be damaged so this pavement needs to be overlay. There is pavement damage that needs overlay activity in the highway, so the pavement is needed to maintain. This study is performed to find the overlay thick of pavement (overlay) by using Falling Weight Deflectometer (FWD) and Benkelman Beam (BB) tools. Overlay thick design is based on Design of Overlay Thick of Flexible Pavement by Deflection Method (Pd T-05-2005-B). The segment of this study is in Jalan Banda Aceh - Medan highway, the data that taken is from the same point between Falling Weight Deflectometer (FWD) and Benkelman Beam (BB). To design the thickness, this investigation needs the result deflection of Falling Weight Deflectometer (FWD) and Benkelman Beam (BB), then the value result is corrected. After the obtain corrected deflection value, the next process is calculating uniformty factor (FK), representative deflection (Dsbl ov), design deflection (Dstl ov), overlay thick (Ho), factor of overlay thickness (Fo), and corrected overlay thick (HT). The result of this study is the overlay thick from Falling Weight Deflectometer (FWD) and Benkelman Beam (BB), it is 5,235 cm for Falling Weight Deflectometer (FWD) and 3,722 cm for Benkelman Beam (BB). The result difference between Falling Weight Deflectometer (FWD) and Benkelman Beam (BB) is 1.513 cm or 28.90% in the percentage.